2009
DOI: 10.1002/j.1834-4453.2009.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine reservoir corrections for Moreton Bay, Australia

Abstract: We present the first direct assessment of marine reservoir effects in the Moreton Bay region using radiocarbon dating of known-age, pre-AD 1950, shell samples from the east coast of Stradbroke Island and archaeological shell/charcoal pairs from Peel Island in Moreton Bay. The resulting ǵR value of 9±19 14 C years for the open ocean conforms to regional values established for northeast Australia of 12±10 14 C years. Negative ǵR values of -65±61 14 C years and -216±94 14 C years for southern Moreton Bay highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 42 publications
(46 reference statements)
0
39
0
Order By: Relevance
“…Values of R, R and 14 C derived from previous work in Moreton Bay (Ulm et al, 2009) and Magnetic Island off the northeastern Australian coast (Lewis et al, 2012) are also plotted in Fig. 3 for comparison.…”
Section: Resultsmentioning
confidence: 98%
“…Values of R, R and 14 C derived from previous work in Moreton Bay (Ulm et al, 2009) and Magnetic Island off the northeastern Australian coast (Lewis et al, 2012) are also plotted in Fig. 3 for comparison.…”
Section: Resultsmentioning
confidence: 98%
“…Recent research has indicated that considerable R variation is possible not just in estuarine or lagoon environments where terrestrial 14 C input is likely (Ulm et al 2009;Petchey and Clark 2011), but also where ocean currents meet continental landmasses, opposing currents, or island chains (Petchey et al 2008). The Bismarck Sea has previously been identified as problematic in this respect (Petchey et al 2004(Petchey et al , 2005McGregor et al 2008).…”
Section: F Petchey and S Ulmmentioning
confidence: 99%
“…Although the archaeological community is now cognizant of the fact that radiocarbon dates obtained on terrestrial and marine samples are not directly comparable, and that an oceanic reservoir correction needs to be applied to dates on marine materials in order to render then comparable with terrestrial ages, the degree of variation in 14 C activity at the local and regional level for marine environments for much of the Australian coastline is still poorly or entirely unknown (Ulm 2006). While regional correction values can be calculated using the Marine Reservoir Correction Database (Reimer and Reimer 2009) for some regions, where there have been no regionally specific studies into marine variability, the use of a generic R correction to calibrate marine and estuarine shell dates entails a level of uncertainty (Ulm et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Some species have wide habitat tolerances. There are many complexities that affect samples at the local level such as upwelling, tidal flushing, terrestrial runoff effects from freshwater input, and local geology (Stuiver and Braziunas 1993;Dye 1994;Ulm 2002;Ulm et al 2009) As some species have wide tolerance levels, the exact collection provenance is essential. Estuarine species have also been shown to produce estuary-specific values that differ significantly from values from species obtained from proximal open coastal marine environments (Ulm 2002).…”
Section: Introductionmentioning
confidence: 99%